Odpowiedzi

  • Użytkownik Zadane
2009-05-28T20:38:54+02:00
-x-(x-3)/3-3>0 /*3
-3x-(x-3)-9>0
-3x-x+3-9>0
-4x-6>0
-4x>6
x<-6/4
x<-3/2
x<-1½

0,1-0,5x<0,2+0,3x /*10
1-5x<2+3x
-5x-3x<2-1
-8x<1
x>-1/8

2/3(6x-3)≥0 /:2/3
6x-3≥0
6x≥3
x≥½

(4x-3)/3-(x+1)/2≥1/6 /*6
2(4x-3)-3(x+1)≥1
8x-6-3x-3≥1
5x-9≥1
5x≥10
x≥2
2009-05-28T20:45:40+02:00
-x-x-3/3-3>0
-2x-1-3>0
-2x-4>0
-2x>0+4
-2x>4|:-2
x<-8

0,1-0,5x<0,2+0,3x
-0,5x-0,3x<0,2-0,1
-0,8x<0,1|:-0,8
x<-8

2/3(6x-3)≥0
4x-2≥0
4x≥0+2
4x≥2|:4
x≥1/2

4x-3/3-x+1/2≥1/6
3x-1 1/2 ≥1/6
3x≥1/6+1 1/2
3x≥1/6+1 3/6
3x≥1 4/6|:3
x≥10/6 *1/3
x≥5/9